BODY FAT, BODY MASS INDEX, BLOOD GLUCOSE LEVELS EXAMINATION PROGRAM AND EDUCATION IN COMMUNITY GROUPS IN MALANG AND MADIUN - Kristianto, Heri; Hany, Alfrina; Widyanto, Rahma Micho; Christina, Kezia; Rieski, Wenny Arta; Putri, Anyelir Viola Fatika (Caring: Jurnal Pengabdian Masyarakat, 2024)
Obesity is one of the risks of Diabetes Mellitus (DM) that requires health screening measures. Different characteristics of rural and urban residents in terms of lifestyle behaviour have an impact on the risk of DM. One of the risk indicators can be seen from the aspects of body mass index (BMI), body fat, and blood glucose levels. The purpose of this paper is to determine the profile of body mass index, body fat, and blood glucose levels between urban and rural residents. Additionally, education and consultation will be provided. Activities were carried out in the form of health screening in Malang City and Madiun Regency for 1 month with a cross sectional design and total sampling according to the presence of participants. Additionally, education and consultation were conducted. The instruments used include a blood glucose meter, HBF-375 body composition meter, and educational videos. Based on the results of measurements in 20 rural people obtained a mean BMI of 23.11kg/m2 (14-61 kg/m2), mean body fat 27.72% (8-41%) and mean blood glucose levels 89.5mg (75-158mg), while measurements in 15 urban people obtained a mean BMI of 27.59 kg/m2 (16-38 kg/m2), mean body fat 32.85% (17-44%) and mean blood glucose levels 123mg (99-216mg). It was concluded that the mean body mass index, body fat percentage, and instantaneous blood glucose levels were higher in urban than rural communities. This can be used as a basis for educational management to prevent the risk of metabolic syndrome. It is necessary to develop intervention management in managing the risk of metabolic syndrome in further community service activities by taking into account regional characteristics.